RETRACTED: Overexpression of SERCA2a Alleviates Cardiac Microvascular Ischemic Injury by Suppressing Mfn2-Mediated ER/Mitochondrial Calcium Tethering - Tian, Feng; Zhang, Ying (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background/Aims: Our previous research has shown that type 2a Sarco/endoplasmic reticulum Ca2+-ATPase (SERCA2a) undergoes posttranscriptional oxidative modifications in cardiac microvascular endothelial cells (CMECs) in the context of excessive cardiac oxidative injury. However, whether SERCA2a inactivity induces cytosolic Ca2+ imbalance in mitochondrial homeostasis is far from clear. Mitofusin2 (Mfn2) is well known as an important protein involved in endoplasmic reticulum ER/mitochondrial Ca2+ tethering and the regulation of mitochondrial quality. Therefore, the aim of our study was to elucidate the specific mechanism of SERCA2a-mediated Ca2+ overload in the mitochondria via Mfn2 tethering and the survival rate of the heart under conditions of cardiac microvascular ischemic injury. Method: In vitro, CMECs extracted from mice were subjected to 6 h of hypoxic injury to mimic ischemic heart injury. C57-WT and Mfn2KO mice were subjected to a 1-h ischemia procedure via ligation of the left anterior descending branch to establish an in vivo cardiac ischemic injury model. TTC staining, immunohistochemistry and echocardiography were used to assess the myocardial infarct size, microvascular damage, and heart function. Results: In vitro, ischemic injury induced irreversible oxidative modification of SERCA2a, including sulfonylation at cysteine 674 and nitration at tyrosine 294/295, and inactivation of SERCA2a, which initiated calcium overload. In addition, ischemic injury-triggered [Ca2+]c overload and subsequent [Ca2+]m overload led to mPTP opening and ΔΨm dissipation compared with the control. Furthermore, ablation of Mfn2 alleviated SERCA2a-induced mitochondrial calcium overload and subsequent mito-apoptosis in the context of CMEC hypoxic injury. In vivo, compared with that in wild-type mice, the myocardial infarct size in Mfn2KO mice was significantly decreased. In addition, the findings revealed that Mfn2KO mice had better heart contractile function, decreased myocardial infarction indicators, and improved mitochondrial morphology. Conclusion: Taken together, the results of our study suggested that SERCA2a-dependent [Ca2+]c overload led to mitochondrial dysfunction and activation of Mfn2-mediated [Ca2+]m overload. Overexpression of SERCA2a or ablation of Mfn2 expression mitigated mitochondrial morphological and functional damage by modifying the SERCA2a/Ca2+-Mfn2 pathway. Overall, these pathways are promising therapeutic targets for acute cardiac microvascular ischemic injury.